Polyphenol-rich curry made with mixed spices and vegetables benefits glucose homeostasis in Chinese males (polyspice study) : a dose – response randomized controlled crossover trial - Haldar, Sumanto (2020)
Purpose: To investigate acute effects of two doses of a polyphenol-rich curry made with seven different spices and four base vegetables, eaten with white rice, on 24 h glucose response, postprandial insulinemia, triglyceridemia and 24 h urinary total polyphenol excretion (TPE). Methods: Randomized, controlled, dose–response crossover trial in healthy, Chinese men [n = 20, mean ± standard deviation (SD) age 23.7 ± 2.30 years, BMI 23.0 ± 2.31 kg/m2] who consumed test meals matched for calories, macronutrients and total vegetables content, consisting either Dose 0 Control (D0C) or Dose 1 Curry (D1C) or Dose 2 Curry (D2C) meal. 24 h glucose concentration was measured using continuous glucose monitoring (CGM), together with postprandial plasma insulin and triglyceride for up to 7 h. Total polyphenol content (TPC) of test meals and urinary TPE were measured using the Folin–Ciocalteu assay. Results: TPC for D0C, D1C and D2C were 130 ± 18, 556 ± 19.7 and 1113 ± 211.6 mg gallic acid equivalent (GAE) per portion served, respectively (p < 0.0001). Compared with D0C meal, we found significant linear dose–response reductions in the 3-h postprandial incremental AUC (iAUC) for CGM glucose of 19% and 32% during D1C and D2C meals respectively (p < 0.05) and non-significant linear dose response reductions in iAUC of insulin (p = 0.089). Notably, we found significant dose-dependent increases in postprandial triglyceride with increasing curry doses (p < 0.01). Significant increases in TPE with increasing curry doses were also observed (p < 0.01). Conclusion: Polyphenol-rich curry intake can improve postprandial glucose homeostasis. The longer term effects remain to be established.